Cytokines in the Pathogenesis of Large Granular Lymphocytic Leukemia - Isabelle, Colleen; Boles, Amy; Chakravarti, Nitin; Porcu, Pierluigi; Brammer, Jonathan; Mishra, Anjali (Frontiers in Oncology, 2022)
Large granular lymphocyte leukemia (LGLL) is a lymphoproliferative disorder of older adults characterized by the clonal expansion of cytotoxic T/natural killer cells due to constitutive pro-survival signaling. In recent years, it has become clear that cytokines and their receptors are aberrantly expressed in LGLL cells. The exact initiation process of LGLL is unknown, although several cytokine-driven mechanisms have emerged. Elevated levels of several cytokines, including IL-15 and PDGF, have been described in LGLL patients. Evidence from humans and animal models have shown that cytokines may also contribute to the co-occurrence of a wide range of autoimmune disease seen in patients with LGLL. The goal of this review is to provide a comprehensive analysis of the link between cytokines and pro-survival signaling in LGLL and to discuss the various strategies and research approaches that are being utilized to study this link. This review will also highlight the importance of cytokine-targeted therapeutics in the treatment of LGLL.